NETosis : immunity, pathogenesis and therapeutics - Rai, Geeta (Elsevier, 2019)
NETosis: Immunity, Pathogenesis and Therapeutics takes a focused approach to the clinical aspects of NETosis and drug development, bringing critical findings. Chapters introduce NETosis, consider mechanisms and antimicrobial strategies regulating NETosis, examine NETosis in neonates, explore the role of NETosis in autoimmunity, delve into NETosis and other diseases, and present therapeutic approaches for dysregulated NETosis. Since Brinkamm, et al, discovered an unrecognized neutrophil anti-microbial mechanism responsible for the extracellular killing of invading pathogens in 2004, the novel process in which nuclear chromatin de-condenses and DNA is ejected into the extra cellular environment, trapping and inactivating tissue pathogens has rapidly evolved.